The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14715/cmb/2020.66.5.26
|View full text |Cite
|
Sign up to set email alerts
|

Guizhi Fuling pills inhibit the proliferation, migration and invasion of human cutaneous malignant melanoma cells by regulating the molecular axis of LncRNA TPT1-AS1 / miR-671-5p

Abstract: The current research was aimed to explore the effects of Guizhi Fuling Pills on the proliferation, migration and invasion of human cutaneous malignant melanoma cells and its regulation on the molecular axis of LncRNA TPT1-AS1 / miR-671-5p. Human cutaneous malignant melanoma cells A375 were cultured in vitro and randomly divided into Con group, Guizhi Fuling pills-L group, Guizhi Fuling pills-M group, Guizhi Fuling pills-H group, Guizhi Fuling pills-H + pcDNA group, Guizhi Poria pills-H + pcDNA-TPT1-AS1 group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…At the molecular level, the present study further demonstrated that 95D cells transfected with miR-671-5p mimics exhibited downregulated expression levels of PCNA, N-cadherin and vimentin, whereas E-cadherin expression levels were upregulated compared with those in the control cells. Guizhi Fuling pills have been reported to inhibit cell proliferation and PCNA expression, which is associated with elevated miR-671-5p expression levels ( 28 ). Tan et al ( 10 ) have demonstrated that the levels of the epithelial marker E-cadherin are upregulated, whereas the levels of vimentin are downregulated in miR-671-5p-transfected MDA-MB-231 cells compared with miR-NC transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, the present study further demonstrated that 95D cells transfected with miR-671-5p mimics exhibited downregulated expression levels of PCNA, N-cadherin and vimentin, whereas E-cadherin expression levels were upregulated compared with those in the control cells. Guizhi Fuling pills have been reported to inhibit cell proliferation and PCNA expression, which is associated with elevated miR-671-5p expression levels ( 28 ). Tan et al ( 10 ) have demonstrated that the levels of the epithelial marker E-cadherin are upregulated, whereas the levels of vimentin are downregulated in miR-671-5p-transfected MDA-MB-231 cells compared with miR-NC transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, high expression of TPT1‐AS1 was positively correlated with advanced TNM stage and poor differentiation, indicating a poor clinical prognosis of PDAC patients. In addition, previous research showed that TPT1‐AS1 functioned as an oncogene in gastric cancer, colorectal cancer, ovarian cancer, cervical cancer, among others 16–19,39,40 …”
Section: Discussionmentioning
confidence: 99%
“…Four major binding sites on the promoter region of TPT1-AS1 were predicted In addition, previous research showed that TPT1-AS1 functioned as an oncogene in gastric cancer, colorectal cancer, ovarian cancer, cervical cancer, among others. [16][17][18][19]39,40 Moreover, functional experiments revealed that TPT1-AS1 could promote pancreatic cancer cell proliferation, invasion, migration, and EMT process in vitro and in vivo. These findings were consistent with those of previous studies and suggested that TPT1-AS1 acted as an oncogenic lncRNA in PDAC.…”
Section: Itgb3 Elevated Tpt1-as1 Expression Through Enhancing Stat3 I...mentioning
confidence: 99%
“…LncRNA-miRNA-mRNA regulatory network plays a significant role in cancer's occurrence, development, and prognosis by regulating downstream target genes and proteins (54)(55)(56)(57). Therefore, targeted therapy drugs can inhibit cancer growth by influencing the regulatory network (58,59). In most types of cancer, such as breast cancer, esophageal cancer, nonsmall cell lung cancer, hepatocellular carcinoma, etc., miR-671 acts as a tumor suppressor and is down-regulated in cancer (60)(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Mir-671 and Osmentioning
confidence: 99%